SMART SPECIALISATION STRATEGY AND POSSIBILITIES FOR ITS IMPLEMENTATION IN THE HEALTHCARE SYSTEM OF THE REPUBLIC OF SERBIA - Curcic, Marijana (HEALTH CARE, 2020)
The aim of this paper is to present the concept of smart specialization strategy according to Research and innovation strategies for smart specialisation RIS3 (S3) of Joint Research Centre European Union as well as some considerations related to its implementation in health care in the Republic of Serbia based on the experiences of neighboring countries, as well as within certain areas. It is necessary that companies, higher education institutions, individual inventors and innovators see the potential for the application of this concept in the health care system of the Republic of Serbia, to determine the extent to which health is a priority area, then to establish regional cooperation with neighboring countries due to similarities, and to become competitive with innovations in the European market.